2018
DOI: 10.1016/j.brainresbull.2017.07.020
|View full text |Cite
|
Sign up to set email alerts
|

Varenicline modulates ethanol and saccharin consumption in adolescent male and female C57BL/6J mice

Abstract: Adolescence is a critical period in brain development that coincides with the initiation of alcohol use. Nicotinic acetylcholine receptors (nAChR) have been shown to modulate ethanol behaviors in adult humans and in animal models; however, the role of these receptors in adolescent ethanol behaviors has not been explored. Throughout adolescence, nAChR expression undergoes large-scale developmental changes which may alter behavioral responses to ethanol. Here we examined the effect of varenicline, a nAChR partia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 48 publications
(94 reference statements)
1
15
0
Order By: Relevance
“…This intake was significantly higher than what has been previously reported with other DID experiments that used lower concentrations. Using 0.1% saccharin, Zhou et al (2019) found intakes around 0.1 g/kg in 4 h (male B6), while Kamens et al (2018) showed drinking up to ∼0.02 g/kg in 2 h (adolescent male and female B6; 0.033% saccharin). Our animals preferred the concentration of 1.06%.…”
Section: ! 12mentioning
confidence: 99%
“…This intake was significantly higher than what has been previously reported with other DID experiments that used lower concentrations. Using 0.1% saccharin, Zhou et al (2019) found intakes around 0.1 g/kg in 4 h (male B6), while Kamens et al (2018) showed drinking up to ∼0.02 g/kg in 2 h (adolescent male and female B6; 0.033% saccharin). Our animals preferred the concentration of 1.06%.…”
Section: ! 12mentioning
confidence: 99%
“…Additionally, previous clinical research suggests that there are sex differences in the efficacy of varenicline, with efficacy being greater in females (McKee et al, 2016). However, previous research with mice shows that there are no sex differences in the effects of varenicline on EtOH drinking (Kamens et al, 2018). Clinical research with naltrexone has also indicated differences in effects for men and women, but overall efficacy appears similar for both sexes (Baros et al, 2008).…”
Section: Discussionmentioning
confidence: 93%
“…Both mecamylamine and nicotine reduce binge DID consumption in male mice 7 . Varenicline has been shown to reduce binge consumption in both male and female C57BL/6J mice 29,30 . Moreover, varenicline requires the α4 nAChR subunit to reduce alcohol consumption, as it does not reduce alcohol consumption in male α4 KO mice 29 .…”
Section: Discussionmentioning
confidence: 99%